Peran Digital Public Relation dalam Mempertahankan Reputasi Brand di Instagram @tokokopituku - Nazila Putri Kyla; Azifah Faza Aghnia; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of Digital Public Relations (DPR) in maintaining public trust in Kopi Tuku's reputation through its Instagram account @tokokopituku. Using qualitative methods with documentation studies, this study analyzed feed posts, captions, comment interactions, and related digital documents. The results show that Kopi Tuku implements a consistent digital communication strategy through simple visuals, humanistic storytelling, and a friendly style of language. This creates a deep perception of authenticity and transparency in the eyes of consumers. Although comment interactions are not too intense, the principle of symmetrical communication is still applied with quick and friendly responses. The consistency of brand values ​​and identity further strengthens public trust, maintaining Kopi Tuku's reputation amidst the intense competition in the coffee industry. This research contributes to the development of digital PR studies and serves as a reference for local coffee industry players in formulating social media-based communication strategies to build closer relationships with consumers.